2009
DOI: 10.1111/j.1464-5491.2009.02738.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of glucose intolerance in cystic fibrosis

Abstract: CFRD is characterized by qualitative and quantitative defects in insulin secretion, but not insulin resistance, and is associated with increased hospital admissions for pulmonary exacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 36 publications
3
51
1
1
Order By: Relevance
“…However, quantitative aspects may not be comparable (8,37,40,46). The largest available adult series (37) displayed an average b-cell function as 70% of control values in the whole CF population and 50% of control values in the subgroup with NGT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, quantitative aspects may not be comparable (8,37,40,46). The largest available adult series (37) displayed an average b-cell function as 70% of control values in the whole CF population and 50% of control values in the subgroup with NGT.…”
Section: Discussionmentioning
confidence: 99%
“…The OGTT is the most common diagnostic test for CFRD and can be repeated yearly. Several studies sampled insulin concentrations during OGTT and analyzed insulin secretion using various algorithms and consistently found reduced and delayed insulin responses (8,37,45,46), even in CF patients with normal glucose tolerance (NGT), supporting the concept that insulin secretory defects are inherent to CF.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin sensitivity in CFRD patients is generally normal or only slightly decreased, except in the settings of acute infectious pulmonary illness or the use of glucocorticoids, when severe insulin resistance is present (28). Furthermore, insulin clearance may also be increased in CF individuals, whether diabetic or not (29).…”
Section: Novel Mechanistic Views On Cfrd Developmentmentioning
confidence: 99%
“…This insulin deficiency largely manifests as post-prandial hyperglycemia due to delayed early insulin secretion, 33 but basal insulin secretion is largely preserved until late in the course of CFRD. In non-diabetic CF individuals, despite NGT, β-cell secretory capacity is reduced.…”
Section: Pathophysiologymentioning
confidence: 99%
“…33,44 Studies using oral and intravenous glucose challenges have reported normal insulin sensitivity, which does not worsen over time. 39,40,45 There is emerging evidence for insulin resistance in CF; a decrease in gluconeogenesis due to insulin signal transduction defect caused by reduction of the transcription factor, FOXO1, was recently discovered by Smerieri et al 46 Insulin resistance emerges during periods of stress and is evident in the impaired insulin-mediated suppression of proteolysis in CF.…”
Section: Pathophysiologymentioning
confidence: 99%